Wood anatomy of three species of Mimosa (Leguminosae-Mimosoideae) occurring in Mexico - Montaño-Arias, Susana Adriana; Camargo-Ricalde, Sara Lucía; Grether, Rosaura (Instituto de Ecología, A.C., 2016)
The morphological diversity of the genus Mimosa and its complex taxonomy have led to the search of other sources of characters, such as those provided by the wood anatomy. The aim of this work was to carry out a comparative study of the wood anatomy of three Mimosa species: M. arenosa, M. lacerata y M. polyantha (Section Batocaulon); the first one is widely distributed along the Pacific slopes in Mexico, Nicaragua, Colombia, Venezuela and Brazil; while the other two are endemic to Mexico. One stem fragment of 80 cm was collected at 80 cm over the soil, from three plants per species. Twenty-five measurements of 15 wood anatomical characters per individual were made. The results suggest that the distinguishing characters among the studied species are: type of porosity, type and prevalence of axial parenchyma, and the presence or absence of vasicentric tracheids and prismatic crystals.